The nanoscale dimension determines the carbonization outcome of electrospun lignin/recycled-PET fibers. (20th July 2019) - Svinterikos, Efstratios; Zuburtikudis, Ioannis; Al-Marzouqi, Mohamed
Graphical abstract: Highlights: The carbonization of lignin/PET fibrous mats yields different carbon morphologies based on their average fiber diameter. Thick submicron fibers (>387 nm) are infusible during carbonization and yield a fibrous carbon structure. Nanofibers of minimum diameter (80 nm) melt and yield a fused carbon structure. The nano-diameter maximizes the heat and mass transfer in the process and the decomposition rate of lignin macromolecules. DSC shows variations in the enthalpy of fusion triggered by the nano-diameter. Abstract: The impact of the nanoscale dimension on the carbonization of electrospun fibers is usually overlooked. In this study, we prove that it is a decisive factor in the outcome of the carbonization process. Six electrospun fibrous mats, each with a different average fiber diameter ranging from 80 nm to 781 nm were fabricated from a lignin/recycled-PET blend of mass ratio 1/1, and their weight loss and decomposition profile were monitored via thermogravimetry. The nano-size effect is evident for those electrospun mats with average diameter lower than 121 nm. These mats exhibit a significantly higher decomposition rate at the 180–260 °C temperature range, which leads to a considerable degree of fusion of the precursor nanofibers. Thus, the carbon structures formed from these mats do not retain the geometrical integrity of their precursor nanofibers. In contrast, no size-effects are manifested to the electrospun samples of average fiber diameter larger than 387 nm, as they decompose at a similar and lower rate between 180 and 260 °C and yield infusible carbon fibers with similar geometry as their corresponding precursor fibers. These results highlight the determinant role of the nano-dimension when carbon fibers are produced through the carbonization of precursor fibers at the sub-micron scale and point out its significance in processes controlled by heat and mass transfer phenomena, as in the case of carbonization.